Endocannabinoids in the treatment of gastrointestinal inflammation and symptoms. (December 2018) - Pesce, Marcella; Esposito, Giuseppe; Sarnelli, Giovanni
Highlights: The use of Cannabis as a complementary and alternative medicine in inflammatory bowel disease has increased due to the evolving policies regarding its legalization. Endocannabinoids in IBD represent both an appealing therapeutic strategy and a captivating scientific dilemma. Results from clinical trials must be carefully interpreted owing to possible reporting-biases related to cannabinoids psychotropic effects. Also, discriminating between symptomatic improvement and the real gain on the underlying inflammatory process is often challenging. Despite these limitations in the current use of these drugs in clinical practice, several novel therapeutic strategies are under consideration to overcome these flaws. Abstract : The evolving policies regarding the use of therapeutic Cannabis have steadily increased the public interest in its use as a complementary and alternative medicine in several disorders, including inflammatory bowel disease. Endocannabinoids represent both an appealing therapeutic strategy and a captivating scientific dilemma. Results from clinical trials have to be carefully interpreted owing to possible reporting-biases related to cannabinoids psychotropic effects. Moreover, discriminating between symptomatic improvement and the real gain on the underlying inflammatory process is often challenging. This review summarizes the advances and latest discovery in this ever-changing field of investigation, highlighting the main limitations in the current use of these drugs in clinical practice and the possible future perspectives to overcome these flaws.